REVITALISASI KETENAGAKERJAAN DAN KESEMPATAN KERJA TERKAIT STRATEGI DAN KEBIJAKAN PEMBANGUNAN PERTANIAN DAN PEDESAAN - ROOSGANDHA ELIZABETH (Program Studi Agribisnis, Fakultas Pertanian, Universitas Udayana Jalan PB.Sudirman Denpasar, Bali, Indonesia. Telp: (0361) 223544 Email: soca@unud.ac.id, 2007)
The fact that a close relationship exist between farmlands and agricultural activitiesbrought about consequence that effort for improving farmers welfare cannot bebased only on technological and institutional improvement. The problem to be facedat present a however, that farmlands tend to be increasingly limited, due tocompetition with other uses of lands, where as people working in the sector ofagriculture is steadily, and absolutely increasing, resulting in an increasingly limitedaverage proprietorship and control of land. These reviews discuss the structure of jobopportunities and income, and their interrelations, as well as the causal relationbetween income expenditure levels of the society, in agricultural and non-agriculturalsector. Productivity of labor as a production factor is considered for more important infarm role obtaining the income, than labor absorption itself. Agro-ecosystem anecological disparities should be identified from variables of job opportunities, income,and society expenditure. Economic development induces changes of sectoraleconomic structure, such from agricultural sector to industrial sector, but isn’taccompanied by labor structural shift. There should be employment also for othersectors, not only for agricultural sectors.